The effect of changing vertical irradiation angle of periapical radiography bisecting technique on the length dimension of mandibular teeth - Wijaya, Andrew Sebastian; Lubis, Muhammad Novo Perwira Satria (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This research is aimed to determine the effect of changing the vertical irradiation angle with a change in angle of +10°, +5°, -5°, -10° in bisecting technique periapical radiography on the length dimension of mandibular teeth. Materials and Methods: This study used a laboratory experimental method with a post test only control group design. The samples used in this study were teeth I1, I2, C, P1, P2, M1, and M2 region 4. All teeth were treated by changing the angle from the standard angle recommended by White and Pharoah with changes of +10°, +5°, -5°, and -10° in each tooth using a Morita Veraview iX 70 Kv, 7mA dental X-ray unit. Results: The results showed that the angle change of -10°, -5° causes foreshortening and +10°, +5° causes elongation. Based on the results of the Saphiro-Wilk and Kruskal-Wallis test, it is known that there are significant differences in the dimensions of tooth length at +10°, +5°, -5°, -10° against changes in the angle 0° or angulation form White and Pharoah (p < 0.05) . Conclusion: There is a significant effect on the change of vertical irradiation angle with angle changes of +10°, +5°, -5°, -10° in bisecting technique periapical radiography on the length dimension of mandibular teeth.